Mothers and their pregnancies: a comparison of three population-based cohorts in Southern Brazil Mães e suas gestações: uma comparação de três coortes de base populacional no Sul do Brasil - Iná S. Santos; Aluísio J. D. Barros; Alicia Matijasevich; Elaine Tomasi; Ricardo S. Medeiros; Marlos R. Domingues; Andréa D. Bertoldi; Fernando C. Barros; Cesar G. Victora (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
Mothers from the 1982, 1993 and 2004 Pelotas birth cohorts were compared across biological, socioeconomic, demographic and reproductive characteristics. Women in the 2004 cohort had higher levels of education, gained more weight during pregnancy, and were heavier at the beginning and end of their pregnancy than mothers who gave birth in 1993 and 1982. There was an important increase in obesity rates (body mass index > 30kg/m²) over the 22 years of the study. Mean parity decreased from 1.3 in 1982 to 1.1 in 2004, with a growing proportion of primiparas and a decline in the proportion of women with > 4 children. The mean birth interval increased from 33.5 months in 1982 to 65.7 in 2004. Smoking during pregnancy decreased from 35.6% in 1982 to 25.1% in 2004. As with other characteristics, the change in smoking status differed according to income, with higher reductions among the wealthiest (from 24.9% to 8.7%) than among the poorest mothers (from 43.7% to 33.6%). In general terms, between 1993 and 2004 there was a decrease in the prevalence of maternal risk factors for unfavorable perinatal outcomes. As mães das coortes de nascimentos de Pelotas de 1982, 1993 e 2004 foram comparadas em relação a características biológicas, sócio-econômicas, demográficas e reprodutivas. As mães da coorte de 2004 tinham escolaridade mais alta, ganharam mais peso durante a gestação e pesavam mais no início e final da gestação, comparadas com as mães de 1993 e 1982. Houve um aumento importante nas taxas de obesidade (índice de massa corporal >30kg/m²) ao longo dos 22 anos do estudo. A paridade média diminuiu de 1,3 em 1982 para 1,1 in 2004, com um aumento na proporção de mulheres primíparas e um declínio na proporção de mulheres com > 4 crianças. O intervalo médio entre nascimentos aumentou de 33,5 meses em 1982 para 65,7 em 2004. O hábito de fumar durante a gravidez diminuiu de 35,6% em 1982 para 25,1% m 2004. Assim como outras características, a mudança no tabagismo mostrou diferenças de acordo com renda familiar, com uma redução menor nas mães de maior renda (de 24,9% para 8,7%), comparadas com as mais pobres (de 43,7% para 33,6%). Em termos gerais, entre 1993 e 2004 houve uma diminuição na prevalência de fatores de risco maternos para desfechos perinatais desfavoráveis.